The structural impacts of enforcement policy on Latino immigrant health - Young, Maria-Elena De Trinidad; Payan, Denise Diaz; Guzman-Ruiz, Iris Y. (Frontiers in Public Health, 2022)
As evidence of the negative health impact of immigration enforcement policy continues to mount, public health research has focused primarily on the psychosocial health mechanisms, such as fear and stress, by which immigration enforcement may harm health. We build on this research using structural vulnerability theory to investigate the structural processes by which enforcement policy may shape Latino immigrants’ health. We conducted qualitative analysis of testimonios from a purposive sample of Latino immigrants (n=14) living in Southern California in 2015, a period of significant federal, state, and local enforcement policy change. Testimonios are a narrative methodology used across the social sciences and humanities to center the voices of oppressed people. Through unstructured testimonio interviews, we explored Latino immigrants’ descriptions of enforcement policy. Respondents’ narratives revealed that singular enforcement experiences were not viewed as the sole manifestation of enforcement, but as part of a system of intersecting physical, legal, institutional, and economic exclusions. These exclusions reinforced respondents’ marginalization, produced instability about the future, and generated a sense of individual responsibility and blame. We propose a framework to inform population health research on intersecting structural health mechanisms. We discuss how physical, legal, institutional, and economic processes may influence health at a distal level, determining Latino immigrants’ day-to-day contexts, exposing them to ongoing and acute enforcement actions, and, ultimately shaping their well-being and security in the US.